The Effect of HEROIC Application on increasing Knowledge and Attitudes of Health Reproductive among Adolescent students in Indonesia - Ni Komang Tri Agustini; Ni Wayan Manik Parwati; Apriani Susmita Sari; I Ketut Swarjana (YCAB Publisher, 2026)
Background: Adolescent health remains a significant concern in Indonesia. Previous studies have revealed that adolescents often lack an adequate understanding of reproductive health. Any program developed should, therefore, aim to improve adolescents’ comprehension of reproductive health issues. Health education delivered via mobile applications has been shown to influence knowledge and attitudes regarding sexual reproductive health. This study employed a health education program using the Health reproductive and Online Interactive Counselling (HEROIC) application as an intervention to improve knowledge and attitudes related to reproductive health among Indonesian adolescents. Objective: This study aims to analyse the effect of the HEROIC application on increasing adolescents’ knowledge and attitude. Methods: A quasi-experimental design with a pre-test-post-test design was used. The sample consisted of 156 adolescents, divided into an intervention group ( 85 participants using the HEROIC application) and a control group (71 participants receiving a booklet). Results: Both the HEROIC application and booklet led to a significant increase in adolescents’ knowledge and attitudes about sexual and reproductive health (p<0.001). However, there were no significant differences in knowledge and attitude improvements between the two groups. Conclusion: There is a constant need to improve knowledge and attitude about sexual and reproductive health. In order to make interventions more effective, it is essential to use the right media to provide health education to adolescents. Keywords: reproductive health; knowledge; attitude; HEROIC application